Analisis Nilai Tambah Pengolahan Dodol Salak Di Desa Bawoleu Kecamatan Tagulandang Utara Kabupaten Kepulauan Siau Tagulandang Biaro - Kadame, Jesika Marsela; Pakasi, Caroline Betsi Diana; Timban, Jean Fanny Junita (Sam Ratulangi University, 2024)
This study aims to analysis the added value of salak dodol processing in Bawoleu Village, North Tagulandang District, Siau Tagulandang Biaro Islands Regency. This research was conducted from August to November 2023. This research uses primary data taken from salak dodol managers, by conducting surveys, interviews and documentation to respondents directly. Secondary data obtained from related agencies, such as the central statistics agency, literature books, literature journals from the internet and the agricultural extension office in bawoleu village, north tagulandang sub-district, siau tagulandang biaro island district. The results showed that salak dodol business is profitable and provides good added value. Salak dodol business in one production process obtained an added value of IDR 114,100/Kg of salak dodol and a profit of Rp94,100/Kg of salak dodol with a value-added ratio of 50.71% classified as high added value because it is above 40%. The largest profit was received by the business owner of 49.52%, then other input contributions of 39.94% and the smallest labor income of 10.52%.